Tyrosyl-DNA-phosphodiesterase I (TDP1) participates in the removal and repair of stabilized-Top2α cleavage complexes in human cells - Borda, Miguel Angel (2015)
Tyrosyl-DNA-phosphodiesterase 1 (TDP1) is a DNA repair enzyme that removes irreversible protein-linked 3′ DNA complexes, 3′ phosphoglycolates, alkylation damage-induced DNA breaks, and 3′ deoxyribose nucleosides. In addition to its extended spectrum of substrates, TDP1 interacts with several DNA damage response factors. To determine whether TDP1 participates in the repair of topoisomerase II (Top2) induced DNA lesions, we generated TDP1 depleted (TDP1kd) human tumoral cells. We found that TDP1kd cells are hypersensitive to etoposide (ETO). Moreover, we established in a chromatin context that following treatment with ETO, TDP1kd cells accumulate increased amounts of Top2α cleavage complexes, removing them with an altered kinetics. We also showed that TDP1 depleted cells accumulate increased γH2AX and pS296Chk1 signals following treatment with ETO. Similarly, cytogenetics analyses following Top2 poisoning revealed increased amounts of chromatid and chromosome breaks and exchanges on TDP1kd cells in the presence or not of the DNA-PKcs inhibitor NU7026. However, the levels of sister chromatid exchanges were similar in both TDP1kd and control non-silenced cell lines. This suggests a role of TDP1 in both canonical non-homologous end joining and alternative end joining, but not in the homologous recombination repair pathway. Finally, micronucleus analyses following ETO treatment revealed a higher frequency of micronucleus containing γH2AX signals on TDP1kd cells. Together, our results highlight an active role of TDP1 in the repair of Top2-induced DNA damage and its relevance on the genome stability maintenance in human cells.